2005
DOI: 10.1134/1.2127992
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional gas-dynamical modeling of changes in the flow structure during the transition from the quiescent to the active state in symbiotic stars

Abstract: The results of 3D modelling of the flow structure in the classical symbiotic system Z Andromedae are presented. Outbursts in systems of this type occur when the accretion rate exceeds the upper limit of the steady burning range. Therefore, in order to realize the transition from a quiescent to an active state it is necessary to find a mechanism able to sufficiently increase the accretion rate on a time scale typical to the duration of outburst development.Our calculations have confirmed the transition mechanis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
21
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 27 publications
8
21
0
Order By: Relevance
“…The potential forces acting in the system were defined using the Roche potential, modified (in a way similar to (Mitsumoto et al, 2005)) to take into account the acceleration of the stellar wind by introducing the parameter Γ, which is equal to zero in regions filled with stellar wind and unity in all other regions:…”
Section: The Modelmentioning
confidence: 99%
“…The potential forces acting in the system were defined using the Roche potential, modified (in a way similar to (Mitsumoto et al, 2005)) to take into account the acceleration of the stellar wind by introducing the parameter Γ, which is equal to zero in regions filled with stellar wind and unity in all other regions:…”
Section: The Modelmentioning
confidence: 99%
“…During the quiescent phase, SSs are undergoing stable hydrogen burning on the surfaces of the WD accretors. The outbursts may be due to either the thermonuclear outbursts on the surfaces of accreting WDs, which are called as symbiotic novae ( Tutukov & Yungelson 1976;Paczyński & Rudak 1980), or accretion-disk instabilities around a nearly steady burning WDs, which are called as multiple outbursts (Mitsumoto et al 2005;Mikoyajewska 2007). Recent reviews of the properties of SSs can be found in Mürset & Schmid (1999) and Mikoyajewska ( , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Results of our 3D calculations described in Mitsumoto et al (2005) winds collision) and there should be areas observable in UV and X-rays. The configuration of a symbiotic system (winds of a symbiotic system have very different characteristics and can be isolated spectroscopically) allows us to estimate parameters of the winds.…”
Section: Introductionmentioning
confidence: 81%